Oedema as a predictor of the incidence of new pressure injuries in adults in any care setting: A systematic review and meta-analysis. (April 2022) - Chaboyer, Wendy; Coyer, Fiona; Harbeck, Emma; Thalib, Lukman; Latimer, Sharon; Wan, Ching Shan; Tobiano, Georgia; Griffin, Bronwyn R; Campbell, Jill L; Walker, Rachel; Carlini, Joan J; Lockwood, Ishtar; et al.
Abstract: Background: Oedema measurement, also termed sub-epidermal moisture measurement is recommended as an adjunct pressure injury prevention intervention in international guidelines because it indicates early tissue damage. Objective: To determine the prognostic value of oedema measurement in predicting future pressure injury in adults in any care setting. Design: Systematic review and meta-analysis. Setting: Participants were recruited from nursing homes or aged care facilities, hospitals, or post-acute facilities. Participants: Adults. Methods: A modified 2-week systematic review was undertaken. Study designs included cohort (prospective and retrospective), case-control, case series if relevant comparisons were reported, randomised controlled trials if the association between oedema measurement and pressure injury was reported, and registry data. Databases searched included: Medical Literature Analysis and Retrieval System Online, The Cumulative Index to Nursing and Allied Health Literature, Excerpta Medica and the Cochrane Library from inception to 13 July 2021 with no language restrictions. Screening, data extraction using Checklist for Critical Appraisal and Data Extraction for Systematic Reviews of Prediction Modelling Studies – Prognostic Factors (CHARMS-PF) and quality assessment using Quality in Prognostic Factor Studies (QUIPS) were undertaken independently by ≥2 authors and adjudicated by another if required. Meta-analyses and meta-regression were undertaken. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results: Six studies ( n  = 483 total) were included. Two studies were set in nursing homes and four in either hospitals or post-acute facilities. Fives studies were prospective cohorts, and one was a randomised control trial. Two studies were assessed as low risk and four studies as moderate risk of bias. The pooled risk ratio in four studies ( n  = 388) for the relationship between oedema and pressure injury cumulative incidence was 18.87 (95% CI 2.13–38.29) and for time to pressure injury was 4.08 days (95% CI 1.64–6.52). Using GRADE, the certainty of the body of evidence was low for all outcomes. Meta-regression indicated that age, gender, and sample size were poor predictors for the association between oedema and pressure injury. Conclusions: Measuring oedema as a predictor for pressure injury development is showing promise but a stronger body of evidence that takes into consideration other prognostic factors is needed to better understand its benefit. Registration: PROSPERO CRD42021267834. Tweetable abstract: Measuring oedema is a promising strategy to prevent pressure injuries but the certainty of evidence for this claim is low.